(untitled) (Asian Journal of Ethnobiology, 2025)
Abstract. Taba, Pant N, Akash. 2025. Traditional plant use and cultural practices sustaining Nyishi livelihoods in Northeast Himalayan region. Asian J Ethnobiol 8: 192-202. The Northeastern Himalaya has a wealth of plants that have been used by the forest dwelling communities. This huge valuable knowledge of these communities is yet to be documented. The present study explored ethnobotanical usage of plants, plant-based traditional skills and technologies by Nyishi tribes in Lower Subansiri District in Arunachal Pradesh, India. An extensive field study was conducted from 2021 to 2023 in the towns of Yazali and Yachuli. Field survey included semi-structured interviews, questionnaire-based survey, focused group discussion, participatory observation, interview of primary respondents and open discussion to provide the data on various traditional plant technologies used in food preparation, cooking, homemade storage structures, fishing, hunting, drying and conservation pattern of related biocultural resources. In the present study, ethnobotanical data were recorded for 39 plant species belonging to 22 families. Information regarding their botanical name, family, common name, local name, and their ethnobotanical uses, along with various indigenous uses of plants, along with traditional tools, traps, utensils, ornaments and accessories, along with food habits used by the Nyishi tribe for sustainability and livelihood. Additionally, observations were made to assess the process of making and using plant technologies.